PROJECT BASED LEARNING : INNOVATION TO IMPROVE THE SUITABILITY OF PRODUCTIVE COMPETENCIES IN VOCATIONAL HIGH SCHOOLS WITH THE NEEDS OF THE WORLD OF WORK - MELDA FAJRA; SUPARNO; SUKARDI; AMBIYAR; RINA NOVALINDA (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2020)
This paper aims to present studies on (1) project-based learning concepts; (2) the theory of learning underlying project-based learning; (3) the implementation of project-based learning; and (4) project-based productive competency learning at Vocational High School. Based on these findings, it can be concluded: (1) Project-based collaborative learning is carried out by creating work or projects related to the competencies that students expect. Project-based learning can help equip students for preparation to enter the world of work; this is because students learn not only in theory but also practice in the field; (2) Project-based learning is a learning model supported or based on constructivist learning theory; (3) the implementation of project-based learning consists of: (a) determination of basic questions; (b) design project planning; (c) draw up a schedule; (d) monitor students and progress; (e) test results; and (f) evaluate the experience, and (4) Project-based learning can be said to be the operationalization of competency-based education and production concepts in vocational high schools. Through project-based learning, students at Vocational High School are introduced to the real atmosphere and meaning of work in the world of work. Thus, the right learning model for vocational high school productive competency is project-based learning.